The Application of Liver Stiffness Measurement in Residents Without Overt Liver Diseases Through a Community-Based Screening Program. Issue 12 (March 2016) - Cheng, Pin-Nan; Chiu, Yen-Cheng; Chiu, Hung-Chih; Chien, Shih-Chieh
Abstract : Abstract: The application of liver stiffness measurement (LSM) by transient elastography (TE) in general population remains to clarify. This cohort study aimed to examine the usefulness of TE and to identify factors associated with significant liver fibrosis in community-based population. We conducted a hepatitis screening program in 2 remote villages of Southern Taiwan. All residents participated voluntarily and received questionnaire evaluation, blood tests, abdominal sonography, and LSM by TE. Residents with any one of following criteria including hepatitis B virus infection, hepatitis C virus infection, more than moderate alcohol drinking, and failure to obtain valid or reliable LSM were excluded. There were 831 residents participated in program. The valid and reliable LSM were obtained in 98.3% and 96.3% of residents, respectively. Finally, a total of 559 residents including 283 residents with nonalcoholic steatotic fatty liver disease (NAFLD) were enrolled for analysis. The mean liver stiffness was 4.9 ± 1.9 kPa. The liver stiffness increased in residents with diabetes mellitus (DM), higher body mass index (BMI), hypertension, abnormal waist–hip circumference ration (WHR), higher waist circumference (WC), and presence of fatty liver. Higher body weight, higher BMI, higher WC, abnormal WHR, abnormal aspartate aminotransferase (AST), abnormal alanine aminotransferase (ALT), and DM were the factors associated with significant fibrosis (liver stiffness ≥7 kPa) in either all participants or NAFLD residents. As determined by multivariate analysis, abnormal AST values and DM were the 2 independent factors in all participants (abnormal AST: OR 3.648, 95% CI 1.134–11.740, P  = 0 .03; DM: OR 2.882, 95% CI 1.282–6.478, P  = 0 .01) and in residents with NAFLD (abnormal AST: OR 4.197, 95% CI 1.154–15.262, P  = 0 .03; DM: OR 3.254, 95% CI 1.258–8.413, P  = 0 .02). LSM by TE is a useful screening tool in community. In residents, who were absence of chronic hepatitis virus infection or consumed less than moderate alcohol drinking, exhibited DM or abnormal AST values may consider a substantial group with significant fibrosis in community.